Pengaruh Gaya Kepemimpinan Dan Komunikasi Interpersonal Terhadap Kepuasan Kinerja Karyawan Di Hotel Asri Podomoro - Tegar, Muhammad; Yuliamir, Henry (Mahesa Research Center, 2025)
This article aims to analyze the influence of leadership style and interpersonal communication on employee performance satisfaction at Hotel Asri Podomoro. The problem is focused on the extent to which these two independent variables can enhance employee performance in the hospitality industry context. The study is based on theories of human resource management, leadership, and organizational communication. Data were collected through questionnaires distributed to employees using purposive sampling and analyzed quantitatively with multiple linear regression. The results indicate that leadership style has a positive and significant effect on employee performance, where leaders who provide direction, role models, and motivation encourage higher work quality. Interpersonal communication was also found to have a more dominant effect, as openness, empathy, and mutual respect foster a harmonious work environment that supports productivity. This study concludes that the combination of appropriate leadership style and effective interpersonal communication is a key factor in improving performance satisfaction. Therefore, human resource management in the hospitality industry should emphasize leadership and communication quality in addition to technical skills.